The Influence of Work Environment on Work Productivity Through Work Discipline as an Intervening Variable on Production Employees of PT BSU Batang Hari - Gintara, Noprian; Sumarni, Sumarni; Aira, Dian Mala Fithriani (Asian Journal of Management Analytics, 2025)
This research aims to analyze the influence of the work environment on work productivity through work discipline as an intervening variable in the production employees of PT Berkat Sawit Utama (BSU) Batang Hari. The method used is quantitative analysis with a sample of 94 respondents selected using a simple random sampling technique from a total population of 122 employees. Data was collected through a Likert scale-based questionnaire, and analysis was carried out using Structural Equation Modeling (SEM) techniques based on Partial Least Square (PLS) via SmartPLS 4 software. The results of the research show that: (1) the work environment has a positive and significant effect on work productivity, (2) the work environment has a positive and significant effect on work discipline, (3) work discipline has a positive and significant effect on work productivity, and (4) work discipline is able to mediate the influence of the work environment on work productivity.